Using Social Media To Support Descriptive Essay Writing And Online Interaction At Undergraduate Level: A Mixed Method Study - Rashid, Muhammad (2024)
This mixed method study aims at investigating the effectiveness of social media as mediating tools to support (a) descriptive essay writing and (b) online interaction at undergraduate level. To substantialize the aim of the study, the researcher selected three intact classes of BS (Bachelor of Science) 4th semester enrolled in a public sector Graduate College in Southern Punjab, Pakistan. To validate the study, a pilot study was conducted prior to the main study.